Professional qualifications: Academic view - Alfredo Soeiro (2017)
At the A+A 2015 in Dusseldorf ISHCCO presented to the experts the qualification framework for Health and Safety Coordinators (HSC) that has produced. ISHCCO represents an European umbrella association of the national professional associations of Health and Safety Coordinators (HSC). One of the statutory aims of ISHCCO is to promote excellence in education, training and professional development in the countries of the national members. Since ISHCCO was founded in 2003 it has been working on the development of such a catalogue of criteria for the promotion and acceptance of qualification framework of Health and Safety Coordinators (HSC). This framework should meet the European and national requirements for those engaged in the activity as Health and Safety Coordinator (HSC) and, as well, international requirements. The system developed by ISHCCO should enable benchmarking based on technical standards, on international and national criteria. For these reasons the decision was made to deduce quality criteria from the European legislation and from respective national implementations and support these with already established professional and international standards of the European Qualification Framework (EQF). The EQF is based on the idea of lifelong learning as central thought and builds on the basis of eight levels as a comparative framework. EQF enables, irrespective of autonomous, institutional or informal learning, a comparability of qualifications of an individual (in this case of the Health and Safety Coordinator (HSC)). The qualification framework is divided in three criteria for knowledge, skills and attitudes referring to the individual qualifications. The EQF offers to an expert the opportunity of classification of their qualifications to a common international level. Besides these criteria it is required the knowledge of national specific regulations that the HSC professional has to acquire and demonstrate. This evidence is verified by an accredited institution facilitating the acquisition of the European Professional Card (EPC). Therefore a specialist in HSC can simply prove their specific qualifications and start their professional activities anywhere in the European Union. The ISHCCO working group has drawn up a proposal, which is based on specific criteria for HSC and places these in relation with the requirements and tasks of related EU directives and of national regulations. In this detailed work the existing and accepted criteria from the area of HSC professionals were examined and compared with the contents of the European Directive 92/57 EU that defines the HSC minimum requirements. The ISHCCO framework also considered national frameworks. The types of projects considered in the HSC framework include requirements for simple projects, medium building construction and civil engineering projects and highly specialized construction projects or major projects. The framework also includes the qualifications for research and development in HSC.